The effect of combined vitamin E succinate and ascorbic acid supplementation on growth and cyclooxygenase expression in murine melanoma (BL6) cells - Van Rooyen, Megan Lynne (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1999)
This thesis examines the effect of combined vitamin E succinate and Asc supplementation on the in vitro growth of a non-malignant monkey kidney (LLCMK) and a malignant melanoma (BL6) cell line, with nutritional concentration ranges of 5-20µg/ml and 25-50µg/ml respectively. Vitamin E and C are thought to interact synergistically to inhibit tumour cell growth by virtue of their antioxidant properties, whereby they quench free radicals and terminate lipid peroxidation. Furthermore vitamin E and C are thought to modulate the biosynthetic pathways in arachidonic acid metabolism at a number of different points. This may also offer a means of regulating tumour cell growth. It is well documented that vitamin E and C are distributed in the lipid and aqueous phases in the cell respectively. However, the cells need to obtain the vitamins from the environment in which they are found in order to exert a growth inhibitory effect. Supplementation of combined vitamin E succinate and Asc on BL6 and LLCMK cells resulted in a significant increase in LLCMK cell growth, and a significant decrease in cell growth was observed in BL6 cells. Vitamin E succinate in its esterified form cannot function as an antioxidant and requires the cleavage of the succinate to become an active antioxidant. The metabolism of vitamin E succinate to form free vitamin E in LLCMK and BL6 cells resulted in the cleavage of the succinate group from the vitamin E molecule in BL6 cells only, thus suggesting that an esterase may be present in BL6 cells. This would allow for a synergistic interaction between the two vitamins. The arachidonic acid cascade generates a family of bioactive lipids that modulate diverse physiological and pathological responses including tumour growth and promotion. The enzyme prostaglandin endoperoxide synthase (PGHS) or cyclooxygenase (Cox) is the key enzyme in the biosynthetic pathway leading to the formation of prostaglandins. Two enzyme isoforms of Cox have been identified, Cox 1 and Cox 2. Supplementation with vitamin E succinate and Asc at a combination 20:25µg/ml respectively resulted in a trend of increasing Cox activity over 12 hours suggesting that vitamin E and Asc have a stimulatory effect on Cox activity in BL6 cells. The inhibitors of Cox 2, dexamethasone, showed a decreasing trend in Cox activity at the 20:25µg/ml combination, while cycloheximide showed an initial stimulatory effect and then a gradual decrease in Cox activity. The elimination of the Cox activity by dexamethasone suggests that transcriptional regulation may be occurring in BL6 cells. We examined by Northern blot analysis whether combined supplementation of vitamin E succinate and Asc caused an elevation of Cox 2 RNA expression in BL6 cells. An inducible effect of Cox 2 was observed after 2 hours of supplementation with a combination of vitamin E succinate and Asc in BL6 cells, however the results are inconclusive and further studies are required to substantiate this finding.
Keywords: Vitamin E; Vitamin C; Melanoma